Przekroczenie uprawnień przez funkcjonariusza Policji a udaremnienie, rozwiązanie lub doprowadzenie do rozwiązania zgromadzenia zorganizowanego w trybie uproszczonym - Ferenz, Jerzy (Studia Prawnoustrojowe, 2019)
Organising of peaceful assemblies and participating in them is one of the fundamental civil freedom in the democratic state based on the rule of law. This paper contains considerations about the matter of offcial duties undertook by police offcers towards participants of assemblies organised in simplifed procedure. It provides an attempt to establish where are the borders of the legality of their acts and when they exceed the border of legality and commit the crime under the article 231 section 1 of the penal code.